Essentialism vs. social constructionism in the study of human sexuality - DeLamater, John D.; Hyde, Janet Shibley (The Journal of Sex Research, 1998)
According to classical essentialism, there are underlying true forms or essences, there is discontinuity between different forms rather than continuous variation, and these true forms are constant over time. Modern essentialism consists of a belief that certain phenomena are natural, inevitable, and biologically determined. We consider sociobiology, evolutionary psychology, genetic research, brain research, and endocrine research as examples of essentialist approaches, focusing particularly on how these research approaches treat sexual orientation and sexual attraction. Social constructionism, in contrast, rests on the belief that reality is socially constructed and emphasizes language as an important means by which we interpret experience. We briefly review social constructionist research on sexual orientation and sexual attraction. Finally, we review examples of conjoint or interactionist research, uniting biological and social influences. We conclude that, although there may be theories and research that conjoin biological and social influences, there can be no true conjoining of essentialism and social constructionism.
Keywords: approches et analyses; comparaison; construction sociale; cours; discipline; essentialisme; histoire et politique; méthodologie; postmodernisme; premier cycle; sciences humaines; sex2283; sociologie; thématiques

The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S.; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M. (American Psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the “gender binary,” played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals’ identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: LGBTQIA2+; activisme; analyse critique; approches et analyses; cours; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; queer; revue de la littérature; sciences humaines; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; études de genres